Urocitellus parryii (Rodentia: Sciuridae). (21st September 2018) - McLean, Bryan S
Abstract: Urocitellus parryii (Richardson, 1825) is a high-latitude sciurid known as the Arctic ground squirrel. The largest of 12 species in the genus Urocitellus, its range extends farther north than any other species of squirrel. It is also the only member of family Sciuridae with a Holarctic distribution. U. parryii is colonial and a conspicuous inhabitant of tundra, meadows, and boreal forests across large tracts of Canada, Alaska, and eastern Siberia. Although the subject of significant research in some parts of its geographic range, aspects of U . parryii biology remain understudied in others, a trend that further characterizes its representation in museum collections both spatially and temporally. Although U. parryii is not currently of conservation concern (listed as "Least Concern" by the International Union for Conservation of Nature and Natural Resources), filling remaining knowledge gaps will be an important component of continued persistence given predicted scenarios of environmental change.